Influência dos diferentes estágios maturacionais na força de jovens praticantes de voleibol - Vasconcelos Teixeira, Rômulo (Educación Física y Ciencia.)
This study aimed to analyze the influence of different maturational stages on performance-related physical fitness components, specifically upper limb explosive strength and jump height. A total of 239 children participated in the study, all of which were volleyball practitioners: 139 were female and 100 were male, aged 10 to 14 years old. Anthropometric assessments and physical capacity tests were performed. For the statistical analysis, Z-score of kurtosis and asymmetry for normality test, and Kruskall-Wallis test, Spearman's correlation and linear regression analysis were used. The girls presented superior results in bone age when compared to boys. Correlations between chronological age and bone age showed similar results. It was concluded that bone age shows a positive correlation with the explosive strength of upper limbs in both sexes.